Inclusive Leadership – International Perspectives and Examples - Vitéz, Kitti (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Book: Stefani, L. & Blessinger, P. (Eds). (2018). Inclusive Leadership in Higher Education. International Perspectives and Approaches. Routledge Taylor & Francis Group. New York and London. p. 214.